Optical measurement system applied to continuous displacement monitoring of long-span suspension bridges - Lages Martins, L. (2014)
This paper provides a general deseription of main issues related to the design of an optieal measurement system applied to continuous displacement monitoring of long-span suspension bridges. The proposed system's architecture is presented and its main components - camera and active targets - are described in terms of geometrical and radiometric characteristics required for long distance measurement of the tridimensional displaeement of the stiffness girder in the middle section ofthe bridge's central span. The intrinsic and extrinsic camera parameterization processes, which support the adopted measurement approach, are explained in a specific section. Since the designed measurement system is intended to perform eontinuous displaeement monitoring in long distance observation framework, particular attention is given to environmental effects, namely, refraction, turbulence and sensor saturation phenomena, which can influence the displacement measurement accuracy. Finally, a measurement uncertainty method is discussed in order to provide a suitable solution for the determination ofthe accuracy related to the proposed measurement approach.